Phylogenetic relationships of the comb-footed spider subfamily Spintharinae (Araneae, Araneoidea, Theridiidae), with generic diagnoses and a key to the genera - Durán-Barrón, César G.; Rosas, María V.; Contreras-Ramos, Atilano (Zootaxa, 2013)
The monophyly of Spintharinae is supported in agreement with previous analysis of Theridiidae by Agnarsson and Arnedo et al. We study the relationships of the genera within Spintharinae. Fourteen species in the genera Chrosiothes, Episinus, Spintharus, Stemmops, and Thwaitesia constituted the ingroup, while five species from the genera Euryopis and Dipoena (Hadrotarsinae), as well as Latrodectus and Steatoda (Latrodectinae), served as outgroup taxa. The character matrix in-cluded 49 morphological characters. Parsimony analyses using several character weighting strategies supported the mono-phyly of Spintharinae with Stemmops as sister to a clade that includes the remaining ingroup taxa. Chrosiothes emerged as sister to Episinus + Spintharus + Thwaitesia which formed a polytomy. The equally weighted, successive weighted, and preferred implied weight topologies, were all logically consistent. A key to the genera of Spintharinae and diagnoses for each genus are given.